2014
DOI: 10.1007/s00338-014-1165-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of near-future temperature increase and ocean acidification on physiology and gonad development in adult Pacific sea urchin, Echinometra sp. A

Abstract: Increased atmospheric CO 2 will have a twofold impact on future marine ecosystems, increasing global sea surface temperatures and uptake of CO 2 (Ocean Acidification). Many experiments focus on the investigation of one of these stressors, but under realistic future climate predictions, these stressors may have interactive effects on individuals. Here, we investigate the effect of warming and acidification in combination. We test for interactive effects of potential near-future (2100) temperature (?2 to 3°C) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
4
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 66 publications
6
67
4
4
Order By: Relevance
“…This highlights the highly partitioned nature of these factors, and suggests that the mechanisms by which each influences metabolism are relatively separated within the physiological pathway. By contrast, other studies of marine invertebrates, albeit often with brief acclimation and narrow size ranges, suggest that the combined metabolic effects of temperature and pH are highly interactive Matoo et al, 2013;Melatunan et al, 2011;Paganini et al, 2014;Uthicke et al, 2014). The increased energetic costs that are associated with a R, metabolic rate (oxygen uptake, mg O 2 h −1 ); M, ash-free dry mass (see also Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This highlights the highly partitioned nature of these factors, and suggests that the mechanisms by which each influences metabolism are relatively separated within the physiological pathway. By contrast, other studies of marine invertebrates, albeit often with brief acclimation and narrow size ranges, suggest that the combined metabolic effects of temperature and pH are highly interactive Matoo et al, 2013;Melatunan et al, 2011;Paganini et al, 2014;Uthicke et al, 2014). The increased energetic costs that are associated with a R, metabolic rate (oxygen uptake, mg O 2 h −1 ); M, ash-free dry mass (see also Fig.…”
Section: Discussionmentioning
confidence: 93%
“…After 69 days exposure, the tropical sea urchin Echinometra sp. A (Uthicke et al, 2014) was found to exhibit no metabolic response to warming or OA in isolation, but there was a slight increase (5.9%) when these were combined. However, the treatments used were moderate (+2-3°C and −0.2 pH units).…”
Section: Effects Of Ocean Acidification On Sea Urchin Metabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…As with a number of taxa, the larval stages of the sea urchin's life cycle are especially vulnerable to reduced OA [31,32]. There have been numerous studies that show a detrimental effect of elevated pCO 2 on the growth, survival, respiration, calcification and gene expression patterns of sea urchin larvae in controlled laboratory experiments [33], including those on Echinometra developmental stages [18,23]. The latter studies showed that under low pH/ high pCO 2 larval development is stunted, and that larvae undergo altered development patterns expressed in arm asymmetry and abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, laboratory studies on the tropical sea urchin genus Echinometra have suggested that a lower seawater pH can induce a range of deleterious responses, including reduced calcification [21], slower somatic growth [22] and impaired reproduction [23]. By contrast, Hazan et al [24] found no change in growth or reproduction in Echinometra viridis over an 11-month exposure to pH (nbs) 7.7, while Moulin et al [25] found no effect on growth, respiration and test properties of Echinometra mathaei exposure to pH (T) 7.6 in large mesocosms over a 13-month exposure.…”
Section: Introductionmentioning
confidence: 99%